Selective release from carbon nanocapsules - Rutte, R (2016)
The optimisation of drug delivery systems is challenging. The approach to drug delivery described here makes use of carbon nanocapsules, including fullerenes and nanotubes. Installation of a targeting moiety to carbon nanocapsules can be achieved via sidewall functionalisation. Carbon nanocapsules also have an unique capacity that can be used for the delivery of payloads such as drugs or imaging agents. In addition, selective release following the application of external stimuli can be used to advance the selectivity of the carbon nanocapsule delivery system. Herein, a photoirradiation reaction triggered reaction that releases a benzoic acid derivative from the carbon surface of fullerenes is described. Fulleropyrazolines were modified with an electron donating aryl group on a nitrogen of the pyrazoline ring. This modification renders the surface functionalisation reversible; the pyrazoline undergoes retro-cycloaddition in the presence of light. Investigations revealed that the method can be used in heterogeneous aqueous solutions. Cathepsin B is a protease that is overexpressed in inflammed cells, such as tumours and arthri- tis. The enzyme selectively cleaves the amino acid sequence phenylalanine-valine-arginine. The coupling of an enzymatically cleavable, designed peptide built around this amino acid sequence to a fulleropyrrolidine was realised. Covalent attachment of this fullerene 'cork' to the carbon nanotube was investigated and analysed by HRTEM/EDX, XPS, XRF, TGA, Raman, and IR spectroscopy. Carbon nanotubes filled with iodide were able to be corked by these modified fullerenes; preliminary studies towards Cathepsin B mediated cleavage were promising. In conclusion, advances in using the unique capacity of carbon nanocapsules for drug delivery were made. In the future, the combination of targeted delivery, achieved by sidewall functionali- sation with a biomolecule, and the triggered release of payload from corked nanotubes may help to open up a new therapeutic field.